Strength, stiffness and ductility of concrete-filled steel columns under axial compression. (15th March 2017) - Wang, Zhi-Bin; Tao, Zhong; Han, Lin-Hai; Uy, Brian; Lam, Dennis; Kang, Won-Hee
Highlights: A simplified model is proposed to predict compressive strength of CFST columns. Models are proposed for compressive stiffness and strain at compressive strength. Capacity reduction factors for the steel and concrete materials are recalibrated. Abstract: Extensive experimental and theoretical studies have been conducted on the compressive strength of concrete-filled steel tubular (CFST) columns, but little attention has been paid to their compressive stiffness and deformation capacity. Despite this, strength prediction approaches in existing design codes still have various limitations. A finite element model, which was previously proposed by the authors and verified using a large amount of experimental data, is used in this paper to generate simulation data covering a wide range of parameters for circular and rectangular CFST stub columns under axial compression. Regression analysis is conducted to propose simplified models to predict the compressive strength, the compressive stiffness, and the compressive strain corresponding to the compressive strength (ductility) for the composite columns. Based on the new strength prediction model, the capacity reduction factors for the steel and concrete materials are recalibrated to achieve a target reliability index of 3.04 when considering resistance effect only.